Down syndrome, paternal age and education: comparison of California and the Czech Republic - Dzurova Dagmara; Pikhart Hynek (BMC, 2005)
Abstract Background The association between maternal age and risk of Down syndrome has been repeatedly shown in various populations. However, the effect of paternal age and education of parents has not been frequently studied. Comparative studies on Down syndrome are also rare. This study evaluates the epidemiological characteristics of Down syndrome in two culturally and socially contrasting population settings, in California and the Czech Republic. Methods The observed live birth prevalence of Down syndrome was studied among all newborns in the California counties monitored by California Birth Defects Monitoring Program from 1996 to 1997, and in the whole Czech Republic from 1994 to 1998. Logistic regression was used to analyze the data. Results A total of 516,745 (California) and 475,834 (the Czech Republic) infants were included in the analysis. Among them, 593 and 251, respectively, had Down syndrome. The mean maternal age of children with Down syndrome was 32.1 years in California and 26.9 years in the Czech Republic. Children born to older mothers were at greater risk of Down syndrome in both populations. The association with paternal age was mostly explained by adjusting for maternal age, but remained significant in the Czech Republic. The association between maternal education and Down syndrome was much stronger in California than in the Czech Republic but parental age influences higher occurrence of Down syndrome both in California and in the Czech Republic. Conclusion The educational gradient in California might reflect selective impact of prenatal diagnosis, elective termination, and acceptance of prenatal diagnostic measures in Californian population.